Economic Analysis of the Fisheries and Agriculture Sectors in Relation to Tanzania's Economic Development - Jackson Bulili Machibya (International Journal of Agricultural Social Economics and Rural Development (Ijaserd), 2025)
The fisheries and agriculture sectors play a pivotal role in Tanzania’s economic development, despite the challenges they face. This paper examines the financial contributions of these sectors, with its novelty lying in a comprehensive analysis of the causal relationships between agriculture and fisheries specific to Tanzania. Using a Vector Autoregression (VAR) approach spanning 1990 to 2021, the study addresses a gap in the existing literature, which often treats these aspects in isolation. The results indicate a statistically significant effect at the 0.05 level, where a one-unit increase in lagged fishing output significantly boosts GDP growth by approximately 1.7% due to enhanced current fishing performance, underscoring the importance of sustainable fishing practices. However, an over-reliance on past high yields can negatively impact GDP, highlighting the risks of overfishing. Conversely, the agriculture sector also makes positive contributions: a one-unit increase in lagged agricultural output is associated with a 0.3% increase in GDP. This result is likewise statistically significant at the 0.05 level. Nevertheless, potential diminishing returns from past yields emphasize the need for innovation and diversification in agricultural practices. Granger causality tests further underscore the interdependencies among the sectors, indicating that improvements in both fishing and agriculture significantly influence GDP growth. These findings suggest that policymakers should prioritize investments in both sectors by increasing funding for agricultural and fisheries research, promoting sustainable modern practices and technology adoption, and providing training for farmers and fishermen to improve productivity, enhance economic resilience, and strengthen food security. Furthermore, this paper contributes to the literature on sustainable economic development in developing countries by providing empirical evidence that highlights the critical role of both sustainable fishing practices and agricultural output in enhancing GDP growth. It reinforces the need for integrated policies that promote environmental sustainability alongside economic performance.